Executive Function-Based Teaching Strategy’s Effect On Secondary School Students’ Understanding Of Force And Physics Metacognition - Abdullah, Mohd Nor Syahrir (2019)
This study was conducted with the aim of introducing EF-based teaching strategy to teach force concepts as well as to evaluate the effectiveness of EF-based teaching strategy on the secondary school students’ understanding of force and physics metacognition.